Produktivitas dan Analisis Usaha di Peternakan Kambing Sumber Barokah, Banjarsari, Surakarta, Jawa Tengah - Muhammad Rizal Ramadhan; Muhammad Arif Darmawan; Wahyu Subagio Saputro (Journal of Applied Agriculture, Health, and Technology, 2024)
Goat are widely raised as meat producer. Goat livestock in Indonesia are generally used as a side business. This study was carried out at Huda Kambing Sumber Barokah (KSB) Farm which is located at Jl. Klodran – Kadipiro, Banjarsari, Surakarta, Central Java. There were 250 goats in KSB. The aim of this study was to analyse and evaluate the management system of rearing and analysis business feasibility at KSB Farm. Seven goats were used as a sample to evaluate the performance productivity. Data included feed intake, body weight, and feed cost were calculated daily for 30 days. Cash flow and investment were taken from interview. The value of ADG; FCR; FCG and FER were 102 g/day; 8,94; Rp. 29.244,00 and 11,15 %. The Value of BEP; BCR; and FER were Rp. 303.639.908,00; 1,4; dan 4 years. From this study, it could be concluded that management system of KSB Farm is good, and the business feasibility analysis showed that this farm is feasible to develop.